2009
DOI: 10.1007/bf03195681
|View full text |Cite
|
Sign up to set email alerts
|

Known mutation (A3072G) in intron 3 of theIGF2 gene is associated with growth and carcass composition in Polish pig breeds

Abstract: IGF2 is one of the genes that control muscle development. Moreover, IGF2 is imprinted, as only the paternal allele is expressed in the offspring. Using real-time PCR for IGF2 genotyping (Carrodegous et al. 2005), we evaluated the frequency of the IGF2 A3072G mutation (Van Laere et al. 2003) in pigs: Polish Landrace (PL, N = 271) and Large White (LW, N = 267). Our results are consistent with previous reports, showing that the A allele is common in breeds subjected to strong selection for lean meat content (A al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 4 publications
4
15
1
Order By: Relevance
“…Our results could be influenced by the absence of GG genotype, and by the low frequency of G allele (0.18) in the studied population of Czech Large White. The low frequency of G allele was observed in other studies in Large White (Vykoukalová et al, 2006;Yang et al, 2006;Oczkowicz et al, 2009). Previously reported associations of the IGF2 gene and lean meat content and backfat thickness in the Black Pied Přeštice pig breed (Civáňová and Knoll, 2007) and in Large White (Vykoukalová et al, 2006) were not confirmed by our study, however the IGF2 gene was associated (P ≤ 0.01) with total EBV as the only one of the analysed genes.…”
Section: And Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Our results could be influenced by the absence of GG genotype, and by the low frequency of G allele (0.18) in the studied population of Czech Large White. The low frequency of G allele was observed in other studies in Large White (Vykoukalová et al, 2006;Yang et al, 2006;Oczkowicz et al, 2009). Previously reported associations of the IGF2 gene and lean meat content and backfat thickness in the Black Pied Přeštice pig breed (Civáňová and Knoll, 2007) and in Large White (Vykoukalová et al, 2006) were not confirmed by our study, however the IGF2 gene was associated (P ≤ 0.01) with total EBV as the only one of the analysed genes.…”
Section: And Discussioncontrasting
confidence: 83%
“…In the IGF2 gene the G allele was associated with higher feed intake and lower average daily gain (Oczkowicz et al, 2009). In our study the AG genotype was associated with higher EBV for reproduction (P ≤ 0.05) and higher total EBV (P ≤ 0.01) in comparison with the AA genotype.…”
Section: And Discussionmentioning
confidence: 99%
“…Porcine IGF2 gene has been intensively studied, because of its strong impact on muscle growth. It was revealed that in pigs IGF2 is imprinted in a tissues specific manner, which means that in some tissues (muscle, kidney) only paternal allele is expressed while in the others (liver and brain) two alleles are present (Li et al, 2008;Van Laere et al, 2003;Wrzeska et al, 2006) Effect of SNP (Single Nucleotide Polymorphism) within intron 3 (IGF2 intron3-g.3072G4A) on muscle growth was previously confirmed in various populations of pigs (Estellé et al, 2005;Fontanesi et al, 2010;Oczkowicz et al, 2009;Van Laere et al, 2003). All experiments concordantly demonstrated significant positive effect of A allele on several carcass traits.…”
Section: Introductionmentioning
confidence: 86%
“…The IGF2 intron3 g.3072G>A substitution has been explicitly identified as a quantitative trait nucleotide and explains a paternally-expressed imprinting QTL (Jeon et al, 1999;Nezer et al, 1999) for muscle growth, fat deposition, and heart size (Van Laere et al, 2003). Several reports have confirmed that pigs carrying the paternal A allele have higher lean growth and lower backfat thickness compared with those having the maternal G allele (Jungerius et al, 2004;Estellé et al, 2005;Oczkowicz et al, 2009). Diarrhea is a major enteric disease in piglets, resulting in higher mortality and treatment costs.…”
mentioning
confidence: 94%